(untitled) (New York, NY., 2017)
The circular economy and the economics of solid waste management are two major chapters in this book. The book also includes haracterization, treatment, and management of different types of solid waste: municipal, institutional, biomedical, e-waste, plastics, and fly ash. Sampling and statistical methods for characterizing waste are dealt with in another major chapter in this book. The fate and transport of contaminants leaching from fly ash were modeled using software like WiscLEACH, while the potential for groundwater contamination was modeled using DRASTIC, and are included in this book
Quản lý và xử lý chất thải độc hại
Keywords: Hazardous wastes,Chất thải nguy hiểm; Management,Quản lý